2014
DOI: 10.1142/s0217732314500886
|View full text |Cite
|
Sign up to set email alerts
|

Holographic superconductors in Born–Infeld electrodynamics and external magnetic field

Abstract: In this paper, we analytically investigate the effect of adding an external magnetic field in presence of Born-Infeld corrections to a holographic superconductor in the probe limit. The technique employed is based on the matching of the solutions to the field equations near the horizon and the asymptotic AdS region. We obtain expressions for the critical temperature and the condensation values explicitly to all orders in the Born-Infeld parameter. The value of the critical magnetic field is finally obtained an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 43 publications
2
43
1
Order By: Relevance
“…We see that the critical temperature decrease with increasing b, which implies that the nonlinear electrodynamics makes the condensation harder. This is consistent with the results of [27,33]. Comparing the results obtained in this table from matching method, with those obtained from the numerical method [34] and those obtained from Sturm-Liouville variational method for Born-Infeld nonlinear electrodynamics [35] shows that the Sturm-Liouville method yields better results than the matching method.…”
Section: (234)supporting
confidence: 89%
See 3 more Smart Citations
“…We see that the critical temperature decrease with increasing b, which implies that the nonlinear electrodynamics makes the condensation harder. This is consistent with the results of [27,33]. Comparing the results obtained in this table from matching method, with those obtained from the numerical method [34] and those obtained from Sturm-Liouville variational method for Born-Infeld nonlinear electrodynamics [35] shows that the Sturm-Liouville method yields better results than the matching method.…”
Section: (234)supporting
confidence: 89%
“…Besides, B c of Ref. [27] does not goes to zero as T → T c , while according to the definition, we should have B c → 0 in the limiting case where T → T c . Using the matching method in the probe limit, some properties of holographic superconductor in Gauss-Bonnet gravity with Born-Infeld electrodynamics and in the presence of a critical magnetic field were investigated in [28].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Considering three types of nonlinear electrodynamics, namely, Born-Infeld, Logarithmic and Exponential nonlinear electrodynamics, and using numerical methods, it has been observed that, in the Schwarzschild AdS black hole background, the higher nonlinear electrodynamics corrections make the condensation harder [25,26]. The effects of an external magnetic field on the holographic superconductors in the presence of nonlinear corrections to the usual Maxwell action were examined in [27,28]. Analytical study of holographic superconductors in Born-Infeld electrodynamics have been carried out in [29][30][31].…”
Section: Jhep04(2016)058mentioning
confidence: 99%